Water-based latex as well as preparation method and construction method thereof
By using an aqueous latex containing styrene butadiene latex, ethylene glycol, hydroxyethyl cellulose, bacterial agent and defoaming agent, combined with specific stirring and construction methods, the problem of poor sealing properties of composite packaging boxes is solved, and efficient sealing performance and good construction properties are achieved.
Patent Information
- Application Number
- CN202411727445.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
AI Technical Summary
When used for sealing composite packaging boxes, existing water-based latexes have problems such as limited construction methods, poor leveling, sagging, excessive thin film for primary construction, poor sealing effect, and low production efficiency.
An aqueous latex is provided, including styrene butadiene latex, ethylene glycol, hydroxyethyl cellulose, bacterial agent and defoaming agent, and a dense adhesive film is formed to improve sealing properties by specific stirring steps and construction methods.
It achieves efficient sealing performance, blocks the penetration of gas and moisture, has good leveling properties, is not prone to sagging, has high elasticity, is not prone to cracking, has adjustable viscosity, is suitable for brushing or spraying construction, and is an environmentally friendly material.
Smart Images

Figure BDA0005159533050000121 
Figure BDA0005159533050000141 
Figure BDA0005159533050000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealing materials, and in particular to a water-based latex and a preparation method and a construction method thereof. Background Art
[0002] There are generally two structural types of fiber reinforced resin composite packaging boxes: one is composed of an upper box body, a lower box body and a box cover; the other is composed of a box body and a box cover. The upper and lower boxes of the upper and lower boxes of the upper and lower boxes and the box cover structure are mainly connected by bolts and sealed with sealants. Since they are not integrally cast, this part is very easy to leak, which becomes a major obstacle to ensuring the sealing of the packaging box; the box cover and the box cover structure of the packaging box are mainly sealed by sealing grooves and sealing strips. The box body slots and the flange edges of the box body and the box cover are the main leakage points of the packaging box.
[0003] At present, packaging box products are mainly wood, metal, plastic, and composite materials. Wood and metal packaging boxes generally do not have airtightness requirements. The airtightness of some high-end metal packaging boxes is mainly guaranteed by welding. Plastic and composite packaging boxes have airtightness requirements. In addition, plastic packaging boxes are mostly thermosetting plastic packaging boxes. Once there is a leak, they are basically judged as scrapped and cannot be repaired. Composite packaging boxes have good airtightness after one-piece molding, and if there is a leak, the leak point can be repaired with traditional paste. Therefore, there is a demand for airtightness repair methods and products for composite packaging boxes.
[0004] Commercially available water-based latex is generally the main raw material for the production of water-based latex coatings and water-based latex adhesives. It has not yet been found to be used for leak repair. In terms of improving the sealing of products, no finished water-based latex products for leak repair have been found on the market. When existing water-based latex products are directly used for leak repair of composite packaging boxes, there are problems such as limited construction methods, poor leveling, sagging, too thin film for one-time construction, poor sealing effect, and low production efficiency. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a water-based latex and a preparation method and a construction method thereof, so as to solve the problems that the existing water-based latex cannot be used for sealing composite material packaging boxes, has limited construction methods, poor leveling, sagging, too thin film in one construction, poor sealing effect, low production efficiency, etc.
[0006] In a first aspect, the present invention provides an aqueous latex for improving the sealing performance of a composite material packaging box. The aqueous latex comprises the following raw materials in parts by weight: 70-85 parts of styrene-butadiene latex, 15-25 parts of ethylene glycol, 2-10 parts of hydroxyethyl cellulose, 0.1-0.4 parts of a sterilizing agent, and 1-2 parts of a defoaming agent.
[0007] Furthermore, the bactericide is isothiazolinone and its derivatives, and the defoamer is defoamer NXZ.
[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned water-based latex for improving the sealing performance of a composite material packaging box, comprising the following steps:
[0009] (1) Weigh each raw material according to its weight and set aside;
[0010] (2) adding hydroxyethyl cellulose and ethylene glycol to styrene-butadiene latex during the first stirring, and increasing the speed to continue the second stirring;
[0011] (3) reducing the rotation speed, adding a sterilizing agent and a defoaming agent during the third stirring, filtering, and obtaining the aqueous latex.
[0012] Furthermore, in step (2), the first stirring speed is 600-800 r / min, and the stirring time is 5-10 min;
[0013] And / or, the second stirring speed is 1300-1800 r / min, and the stirring time is 20-50 min. Further, in step (3), the third stirring speed is 800-1300 r / min, and the stirring time is 5-15 min.
[0014] In a third aspect, the present invention provides a construction method of the above-mentioned water-based latex, comprising applying the water-based latex on the air leaking area.
[0015] Furthermore, the method includes applying glue to the mold seam of the upper and lower box bodies of the composite material packaging box, or applying glue to the flange between the box body and the box cover, or applying glue to the entire box.
[0016] Furthermore, the glue coating method includes first coating along the X-axis direction, drying for the first time, coating for the second time along the Y-axis direction, drying for the second time, coating for the third time along the X-axis direction, drying for the third time to form a glue film.
[0017] Furthermore, the first drying time is 20 to 40 minutes, the second drying time is 20 to 40 minutes, and the third drying time is 1 to 3 hours.
[0018] Furthermore, the thickness of the adhesive film is 0.2-1 mm.
[0019] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0020] (1) The main film-forming substance in the water-based latex of the present invention is styrene butadiene latex, which will form a dense styrene butadiene film after curing, playing a film-forming role. Hydroxyethyl cellulose plays a vital role in latex. Its good emulsification and suspension properties can react with latex particles to promote the uniform dispersion of particles in the emulsion. In addition, hydroxyethyl cellulose can also reduce the occurrence of sedimentation, and promote the emulsion to maintain its own shape and stability. Ethylene glycol is used as a solvent. By adding a defoamer and a sterilizing agent, the various raw materials work synergistically to form a water-based latex product with stable shape, low gas content, and not easy to deteriorate. After use, a dense rubber film layer can be formed, which has excellent sealing performance, can effectively block the penetration of gas and water, and has good film-forming effect. During spray construction, it has good leveling properties and is not easy to sag. It has high elasticity and is not easy to crack. The viscosity is adjustable, which meets the requirements of brushing or spraying, and is easy to construct. It is a water-based polymer material and is environmentally friendly.
[0021] (2) The aqueous latex prepared by the above-mentioned preparation method of the present invention has a low gas content, has strong stability, and is not prone to sedimentation and demulsification. In addition, the latex is also anti-mold and is not prone to mildew.
[0022] (3) The construction method of the present invention adopts X-axis and Y-axis coating, which can ensure the intersection of the coating surfaces and fully cover the coating intersection, thereby improving the overall coating integrity and high construction efficiency.
[0023] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description. DETAILED DESCRIPTION
[0024] The embodiments of the present invention are used to illustrate the principles of the present invention rather than to limit the scope of the present invention.
[0025] A specific embodiment of the present invention discloses an aqueous latex for improving the sealing performance of a composite material packaging box. The aqueous latex comprises the following raw materials in parts by weight:
[0026] 70-85 parts of styrene-butadiene latex, for example, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts;
[0027] 15-25 parts of ethylene glycol, for example, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts;
[0028] Hydroxyethyl cellulose 2-10 parts, for example, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts;
[0029] 0.1-0.4 parts of disinfectant, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts;
[0030] Defoaming agent 1-2 parts, for example, 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2 parts.
[0031] The main film-forming substance in the water-based latex of the present invention is styrene butadiene latex, which forms a dense styrene butadiene film after solidification, and plays a film-forming role. Hydroxyethyl cellulose plays a crucial role in the latex, and its good emulsification and suspension can act on latex particles, prompting the particles to be evenly dispersed in the emulsion. In addition, hydroxyethyl cellulose can also reduce the sedimentation phenomenon, prompting the emulsion to maintain its own form and stability. Ethylene glycol is used as a solvent. By adding a defoamer and a sterilizing agent, the synergistic effect of various raw materials of the present invention can form a water-based latex product with stable form, low gas content, and not easy to deteriorate. After use, a dense rubber film layer can be formed, which has excellent sealing performance, can effectively block the penetration of gas and water, and has good film-forming effect. During spraying construction, it has good leveling property, is not easy to have sagging phenomenon, has high elasticity, is not easy to crack, has adjustable viscosity, meets brushing or spraying, is convenient to construct, and is a water-based polymer material and is environmentally friendly.
[0032] Specifically, the bactericide is isothiazolinone and its derivatives, and the defoamer is defoamer NXZ.
[0033] Another specific embodiment of the present invention discloses a method for preparing the above-mentioned water-based latex for improving the sealing performance of a composite material packaging box, comprising the following steps:
[0034] (1) Weigh each raw material according to its weight and set aside;
[0035] (2) adding hydroxyethyl cellulose and ethylene glycol to styrene-butadiene latex during the first stirring, and increasing the speed to continue the second stirring;
[0036] (3) reducing the rotation speed, adding a sterilizing agent and a defoaming agent during the third stirring, filtering, and obtaining the aqueous latex.
[0037] Specifically, in step (2), the rotation speed of the first stirring is 600-800 r / min, and the stirring time is 5-10 min.
[0038] Specifically, in step (2), the second stirring speed is 1300-1800 r / min, and the stirring time is 20-50 min.
[0039] It should be noted that in step (2), stirring is first performed at a low speed and then at a higher speed in order to achieve more complete mixing. In addition, it can also reduce the particle size of the latex particles and achieve more uniform dispersion.
[0040] Specifically, in step (3), the rotation speed of the third stirring is 800-1300 r / min, and the stirring time is 5-15 min.
[0041] The rotation speed is reduced in this step, on the one hand, to allow the gas to converge and the defoaming agent to remove the bubbles in the latex, and on the other hand, to avoid mixing of gas under high-speed stirring. In addition, long-term high-speed stirring has the risk of demulsification.
[0042] Specifically, in step (3), the filtration is performed using 40-80 mesh silk filtration.
[0043] The aqueous latex prepared by the preparation method of the present invention has low gas content, strong stability, and is not prone to sedimentation and demulsification. In addition, the latex is also anti-mold and is not prone to mildew.
[0044] The aqueous latex of the present invention can be diluted to a desired viscosity by adding water according to actual needs, and then applied by brushing or spraying. Specifically, when applied by brushing, the viscosity of the diluted aqueous latex is 1000-1200 mPa·s. When applied by spraying, the viscosity of the diluted aqueous latex is 700-900 mPa·s.
[0045] The specific dilution method is as follows:
[0046] (I) Material collection: Take an appropriate amount of water-based latex and put it into a clean and uncontaminated bucket (no contamination from solvents such as acetone and alcohol); Take an appropriate amount of distilled water and put it into a clean and uncontaminated bucket (no contamination from solvents such as acetone and alcohol);
[0047] (II) Dilution: Add a stirring device to a bucket of water-based latex, stir, add a small amount of distilled water to the water-based latex, add a small amount of distilled water after stirring, and repeatedly add distilled water to the water-based latex in small amounts until the viscosity reaches a level that can be applied by brush or spray;
[0048] (III) Filtration: Use a filter to filter out impurities in the diluted aqueous latex or flocs produced by demulsification.
[0049] Another specific embodiment of the present invention discloses a construction method of the above-mentioned water-based latex, which includes coating the water-based latex on the air leakage site.
[0050] Preferably, the method comprises applying glue to the mold seam of the upper and lower box bodies of the composite material packaging box, or applying glue to the flange between the box body and the box cover, or applying glue to the entire box.
[0051] Specifically, the glue coating method includes first coating along the X-axis direction, drying the first time, coating the second time along the Y-axis direction, drying the second time, coating the third time along the X-axis direction, drying the third time to form a glue film.
[0052] X-axis and Y-axis coating can ensure that the coating surfaces intersect and fully cover the coating junctions, thus improving the overall coating integrity.
[0053] Wherein, the coating includes spraying or brushing.
[0054] Preferably, the first drying time is 20 to 40 minutes, the second drying time is 20 to 40 minutes, and the third drying time is 1 to 3 hours.
[0055] It should be noted that three times of coating is to promote coating integrity. There may be places that cannot be coated once. More than three times will reduce efficiency, and too thick a coating will waste raw materials. Drying is curing, which is to dry thoroughly and have a better film-forming effect. The first and second drying time is basically 80%-90% of the curing time. You can apply the coating for the third time, but the effect is not the best. The short time of the first two times is also conducive to construction and improves efficiency.
[0056] Preferably, the thickness of the adhesive film is 0.2-1 mm.
[0057] In a specific embodiment, the gluing operation of the upper and lower box mold seams is as follows:
[0058] (a1) Repair and polish: Polish the upper and lower mold seams of the packaging box within a width of 100 to 400 mm to make them smooth;
[0059] Specifically, the inner surface of the box within the range is polished to make it smooth without obvious defects, and the defective parts are repaired with atomic putty and polished again;
[0060] (b1) Cleaning and protection: Clean the polished surface, remove the dust on the surface, and perform protective treatment on the unpolished part;
[0061] (c1) coating the clean surface with the aqueous latex.
[0062] In a specific implementation, the specific operation of applying glue on the flange of the box body and the box cover is as follows:
[0063] (a2) Chamfering: Chamfer the right angles of the flanges of the box body and the box cover. Preferably, the chamfer is rounded, and the chamfer is about R3;
[0064] The contact area at the right angle is a line. Due to gravity and other reasons, the coating here will be too thin, increasing the risk of air leakage. The rounded corners increase the contact area and ensure the coating thickness.
[0065] (b2) Repair and polish: Polish the upper and lower 50 to 200 mm width of the flange connection of the packaging box to make it smooth;
[0066] Specifically, the polishing positions include the box cover, the upper surface of the box flange, the inner surface of the box, and the box sealing groove;
[0067] (c2) Cleaning and protection: Clean the polished surface, remove the dust on the surface, and perform protective treatment on the unpolished parts;
[0068] (d2) coating the clean surface with the aqueous latex.
[0069] In a specific embodiment, the specific operation steps of gluing the entire box are as follows:
[0070] (a3) Repair and polish: repair and polish the inside of the packaging box;
[0071] Specifically, the inner surface of the packaging box is polished to make it smooth without obvious defects, and the defective parts are repaired with atomic putty and polished again;
[0072] (b3) Cleaning: Clean the inner surface of the repaired and polished packaging box and remove surface dust;
[0073] (c3) coating the clean surface with the aqueous latex.
[0074] The technical solution of the present invention is further explained below in conjunction with specific embodiments.
[0075] Example 1
[0076] The aqueous latex used to improve the sealing performance of a composite material packaging box of this embodiment comprises the following raw materials in parts by weight: 80 parts of styrene-butadiene latex, 17 parts of ethylene glycol, 5 parts of hydroxyethyl cellulose, 0.3 parts of a fungicide isothiazolinone, and 1.5 parts of a defoaming agent NXZ.
[0077] The preparation method of the water-based latex of the present embodiment comprises the following steps:
[0078] (1) Weigh each raw material according to its weight and set aside;
[0079] (2) adding hydroxyethyl cellulose and ethylene glycol to styrene-butadiene latex at a stirring speed of 700 r / min for 5 min, increasing the speed to continue stirring, increasing the speed to 1500 r / min, and stirring for 30 min;
[0080] (3) reducing the rotation speed to 1300 r / min, adding the bactericide and defoamer while continuing to stir, stirring for 10 minutes, filtering with 40 mesh silk to obtain the aqueous latex.
[0081] Example 2
[0082] The aqueous latex used to improve the sealing property of a composite material packaging box of this embodiment comprises the following raw materials in parts by weight: 70 parts of styrene-butadiene latex, 25 parts of ethylene glycol, 2 parts of hydroxyethyl cellulose, 0.4 parts of fungicide isothiazolinone and 1.1 parts of defoaming agent NXZ.
[0083] The preparation method of the water-based latex of the present embodiment comprises the following steps:
[0084] (1) Weigh each raw material according to its weight and set aside;
[0085] (2) adding hydroxyethyl cellulose and ethylene glycol to styrene-butadiene latex at a stirring speed of 600 r / min for 7.5 min, increasing the speed to continue stirring, increasing the speed to 1300 r / min, and stirring for 50 min;
[0086] (3) reducing the rotation speed to 800 r / min, adding the bactericide and defoamer while continuing to stir, stirring for 5 minutes, filtering with 60-mesh silk to obtain the aqueous latex.
[0087] Example 3
[0088] The aqueous latex used to improve the sealing performance of a composite material packaging box of this embodiment comprises the following raw materials in parts by weight: 85 parts of styrene-butadiene latex, 15 parts of ethylene glycol, 10 parts of hydroxyethyl cellulose, 0.1 parts of a fungicide isothiazolinone, and 2 parts of a defoaming agent NXZ.
[0089] The preparation method of the water-based latex of the present embodiment comprises the following steps:
[0090] (1) Weigh each raw material according to its weight and set aside;
[0091] (2) adding hydroxyethyl cellulose and ethylene glycol to styrene-butadiene latex at a stirring speed of 800 r / min for 10 min, increasing the speed to continue stirring, increasing the speed to 1800 r / min, and stirring for 20 min;
[0092] (3) reducing the rotation speed to 1000 r / min, adding the bactericide and defoamer while continuing to stir, stirring for 15 minutes, filtering with 80 mesh silk to obtain the aqueous latex.
[0093] Comparative Example 1
[0094] The raw materials and preparation method of the water-based latex of this comparative example are the same as those of Example 1, except that no styrene-butadiene latex is added to the raw materials. This comparative example cannot form a stable latex and cannot be used.
[0095] Comparative Example 2
[0096] The raw materials and preparation method of the aqueous latex of this comparative example are the same as those of Example 1, except that hydroxyethyl cellulose is not added to the raw materials.
[0097] Comparative Example 3
[0098] The raw materials and preparation method of the water-based latex of this comparative example are the same as those of Example 1, except that the addition amount of styrene-butadiene latex is 65 parts.
[0099] Comparative Example 4
[0100] The raw materials and preparation method of the aqueous latex in this comparative example are the same as those in Example 1, except that the amount of hydroxyethyl cellulose added is 15%.
[0101] Comparative Example 5
[0102] The raw materials and preparation method of the water-based latex in this comparative example are the same as those in Example 1, except that the styrene-butadiene latex is replaced by chloroprene latex.
[0103] Comparative Example 6
[0104] The raw materials of the water-based latex of this comparative example are the same as those of Example 1, except that in the preparation method, the raw materials are directly mixed and stirred evenly to obtain the water-based latex. This comparative example cannot form a stable latex and cannot be used.
[0105] Preparation Example 1
[0106] The viscosity of the aqueous latex prepared in Examples 1-3 and Comparative Examples 1-6 was tested respectively, and the aqueous latex with a viscosity of >1500 mPa·s was diluted, and the diluted aqueous latex was used for spraying, and the viscosity was 700-900 mPa·s. The latex with a viscosity lower than 700 mPa·s was directly sprayed, and the specific dilution method was as follows:
[0107] (I) Take 1 kg of the aqueous latex prepared in Examples 1-3 and Comparative Examples 1-6 respectively, and put them into a clean and pollution-free bucket (no contamination from solvents such as acetone and alcohol); take 300 g of distilled water into a clean and pollution-free bucket (no contamination from solvents such as acetone and alcohol);
[0108] (II) Dilution: Add a stirring device to a bucket containing water-based latex, stir at a speed of 700 r / min, add a small amount of distilled water to the water-based latex, add a small amount of distilled water after stirring, and repeat this process of adding 300 g of distilled water to the water-based latex in small amounts several times until the viscosity reaches a sprayable state;
[0109] (III) Filtration: Use a 40-mesh filter to filter out impurities or flocs produced by demulsification in the diluted aqueous latex to obtain diluted aqueous latexes, which are respectively recorded as test samples 1-3 and control samples 1-6.
[0110] Application Example 1
[0111] In order to solve the problem of air leakage at the mold seam of the upper and lower boxes of the packaging box, the test samples 1-3 and the control samples 1-6 prepared in Preparation Example 1 were coated on the mold seam of the upper and lower boxes of the composite material packaging box, respectively. The coating was sprayed, and the specific coating method was as follows:
[0112] (a1) Repair and polish: Polish the upper and lower 300mm width of the mold seam of the packaging box to make it smooth;
[0113] Specifically, the inner surface of the box within the range is polished to make it smooth without obvious defects, and the defective parts are repaired with atomic putty and polished again;
[0114] (b1) Cleaning and protection: Clean the polished surface, remove the dust on the surface, and perform protective treatment on the unpolished part;
[0115] (c1) coating the clean surface with the aqueous latex, wherein the specific coating method comprises first coating along the X-axis direction, drying the first coating for 30 minutes, coating the second coating along the Y-axis direction, drying the second coating for 30 minutes, coating the third coating along the X-axis direction, and drying the third coating for 2 hours to form a film with a thickness of 0.5-1 mm.
[0116] The box in this application example is a glass fiber reinforced vinyl resin composite material packaging box, length * width * height: 7900mm * 750mm * 750mm. The packaging box has an end door and cover structure. The upper box body and the lower box body are locked by 78 mold bolts. The upper surface of the upper and lower box flanges is coated with sealant. The mold seam is manually pasted with short-cut felt twice. Appropriate holes of φ2mm (non-through holes) are drilled at the mold seam to ensure air leakage between the holes.
[0117] When testing the air tightness of the box in this application example, the pressure was filled to 10 kPa during the test, and the pressure drop was observed for 2 hours. After 2 hours, the pressure drop was 0, proving that the air tightness was good. The results are shown in Table 1.
[0118] According to GB / T 13936-2014 “Determination of tensile shear strength of bonding between vulcanized rubber and metal”, the adhesion between the film and the box and the elasticity of the film in this application example were tested. The results are shown in Table 1.
[0119] The leveling property of the film in this application example was tested according to GB / T 1750-1979 “Determination of leveling property of coatings”. The results are shown in Table 1.
[0120] For all test items, the consistency of spraying technique and number of spraying times shall be ensured when preparing samples. When testing airtightness, it shall be ensured that there are no other air leakage points in the box except the artificial air leakage points at the mold joint.
[0121] Table 1
[0122]
[0123] As shown in Table 1, for the leakage phenomenon of the upper and lower box body joint seams of the packaging box, the test samples 1-3 and control samples 1-5 prepared in Preparation Example 1 were coated and tested for comparison. It can be seen that the control sample 1 without latex cannot form a film and cannot be used; by comparing the test samples 1-3, it can be seen that the air tightness of the test sample 1 is the best, and the comprehensive performance is also the best. By comparing the test sample 1 with the control sample 1-5, it can be seen that the air tightness of the test sample 1 is the best, and the comprehensive performance is higher. Compared with the test sample 1, the sealing, bonding force and elongation at break of the water-based latex prepared under the formula of the present invention are poor in the control sample 1-4. Compared with the test sample 1, the control sample 5 is similar to the test sample 1, but the sealing, bonding force and elongation at break of the formula of the present application are replaced by the chloroprene latex, and the elasticity of the film is poor, which is not conducive to the leak repair effect. It is shown that the various substances of the present invention are synergistic, can form a stable form and have excellent sealing performance, can effectively block the penetration of gas and moisture, and have a good film-forming effect.
[0124] Application Example 2
[0125] In order to solve the air leakage problem at the flange edge of the box body and the box cover, the test samples 1-3 and the control samples 1-6 prepared in Preparation Example 1 were coated on the box body and the box cover flange of the composite material packaging box, respectively. The coating was sprayed. The specific coating method is as follows:
[0126] (a2) Chamfering: Chamfer the right angles of the flanges of the box body and the box cover, and the chamfer should be about R3;
[0127] (b2) Repair and polish: Polish the upper and lower 150mm width positions of the flange connection of the packaging box to make it smooth;
[0128] Specifically, the polishing positions include the box cover, the upper surface of the box flange, the inner surface of the box, and the box sealing groove;
[0129] (c2) Cleaning and protection: Clean the polished surface, remove the dust on the surface, and perform protective treatment on the unpolished parts;
[0130] (d2) coating the clean surface with the aqueous latex, wherein the specific coating method comprises first coating along the X-axis direction, drying the first coating for 30 minutes, and then coating the second coating along the Y-axis direction, drying the second coating for 30 minutes, and then coating the third coating along the X-axis direction, and drying the third coating for 2 hours to form a film with a thickness of 0.5-1 mm.
[0131] The box in this application example is a glass fiber reinforced unsaturated resin-based composite material packaging box, with a length*width*height of 900mm*900mm*500mm. The packaging box has an upper and lower cover structure, and the cover and the box body are locked by 12 buckles. A sealing strip is provided on the upper surface of the box flange to test the air tightness of the box in this application example.
[0132] When testing the air tightness of the box in this application example, appropriate holes of φ2mm (non-through holes) are drilled from the inside and outside of the flange. The holes are preferably drilled through the skin to contact the internal pre-embedded to ensure air leakage between the holes. During the test, the pressure is filled to 10kpa, and the artificial air leakage point position on the flange edge of the packaging box is sprayed with bubble water. If no bubbles are generated, it proves that the air tightness is good. The results are shown in Table 2.
[0133] According to GB / T 13936-2014 “Determination of tensile shear strength of bonding between vulcanized rubber and metal”, the adhesion between the film and the box and the elasticity of the film in this application example were tested. The results are shown in Table 2.
[0134] The leveling property of the film in this application example was tested according to GB / T 1750-1979 “Determination of leveling property of coatings”. The results are shown in Table 2.
[0135] For all test items, when preparing samples, ensure the consistency of spraying technique and number of spraying times.
[0136] Table 2
[0137]
[0138] As shown in Table 2, for the leakage phenomenon of the flange edge of the packaging box, the test samples 1-3 prepared by Preparation Example 1 and the control samples 1-5 were coated and tested for comparison. It can be seen that the control sample 1 without latex cannot form a film and cannot be used; by comparing the test samples 1-3, it can be seen that the three test samples have good air tightness, and the comprehensive performance of the test sample 1 is the best. By comparing the test sample 1 with the control samples 1-5, it can be seen that the test sample 1 has the best air tightness and high comprehensive performance. Compared with the test sample 1, the performance of the water-based latex prepared under the formula of the present invention is poor. Compared with the test sample 1, the control sample 5 is similar to the test sample 1, but the bonding force and elongation at break of the formula of the present application replaced by the chloroprene latex are poor, and the elasticity of the film is poor, which is not conducive to the leak repair effect. It shows that the various substances of the present invention are synergistic, can form a stable form and have excellent sealing performance, can effectively block the penetration of gas and moisture, and have a good film-forming effect.
[0139] Application Example 3
[0140] The test samples 1-3 and control samples 1-6 prepared in Preparation Example 1 were coated on the entire body of the composite material packaging box, respectively. The specific operation steps of coating the entire box with glue are as follows:
[0141] (a3) Repair and polish: repair and polish the inside of the packaging box;
[0142] Specifically, the inner surface of the packaging box is polished to make it smooth without obvious defects, and the defective parts are repaired with atomic putty and polished again;
[0143] (b3) Cleaning: Clean the inner surface of the repaired and polished packaging box and remove surface dust;
[0144] (c3) coating the clean surface with the aqueous latex, wherein the specific coating method comprises first coating along the X-axis direction, drying the first coating for 30 minutes, coating the second coating along the Y-axis direction, drying the second coating for 30 minutes, coating the third coating along the X-axis direction, and drying the third coating for 2 hours to form a film with a thickness of 0.5-1 mm.
[0145] The box in this application example is a glass fiber reinforced vinyl resin composite material packaging box, length * width * height: 7900mm * 750mm * 750mm. The packaging box has an end door and cover structure. The upper box body and the lower box body are locked by 78 mold bolts. The upper surface of the upper and lower box flanges is coated with sealant. The mold seam is manually pasted with short-cut felt twice. Appropriate holes of φ2mm (non-through holes) are drilled inside and outside the box body, preferably to the embedded parts, to ensure that there is no leakage between the holes.
[0146] When testing the air tightness of the box in this application example, the pressure was filled to 10 kPa during the test, and the pressure drop was observed for 2 hours. After 2 hours, the pressure drop was 0, proving that the air tightness was good. The results are shown in Table 3.
[0147] According to GB / T 13936-2014 “Determination of tensile shear strength of bonding between vulcanized rubber and metal”, the adhesion between the film and the box and the elasticity of the film in this application example were tested. The results are shown in Table 3.
[0148] The leveling property of the film in this application example was tested according to GB / T 1750-1979 “Determination of leveling property of coatings”. The results are shown in Table 3.
[0149] For all test items, when preparing samples, ensure the consistency of spraying technique and number of spraying times.
[0150] Table 3
[0151]
[0152] As shown in Table 3, for the leakage of the whole box of the packaging box, the test samples 1-3 and control samples 1-5 prepared in Preparation Example 1 were coated and tested for comparison. It can be seen that the control sample 1 without latex cannot form a film and cannot be used; by comparing the test samples 1-3, it can be seen that the three test samples all have good sealing properties, and the comprehensive performance of the test sample 1 is the best. By comparing the test sample 1 with the control samples 1-5, it can be seen that the test sample 1 has the best tightness. Compared with the test sample 1, the control sample 5 has similar properties to the chloroprene latex, but the formula of the present application is replaced with the poor adhesion and elongation at break of the chloroprene latex, and the film elasticity is poor, which is not conducive to the leak repair effect.
[0153] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A water-based latex for improving the sealing performance of a composite material packaging box, characterized in that: The water-based latex comprises the following raw materials in parts by weight: 70-85 parts of styrene-butadiene latex, 15-25 parts of ethylene glycol, 2-10 parts of hydroxyethyl cellulose, 0.1-0.4 parts of a sterilizing agent and 1-2 parts of a defoaming agent.
2. The aqueous latex for improving the sealing performance of a composite material packaging box according to claim 1, characterized in that: The bactericide is isothiazolinone and its derivatives, and the defoamer is defoamer NXZ.
3. A method for preparing an aqueous latex for improving the sealing performance of a composite material packaging box according to claim 1 or 2, characterized in that: The steps include: (1) Weigh each raw material according to its weight and set aside; (2) adding hydroxyethyl cellulose and ethylene glycol to styrene-butadiene latex during the first stirring, and increasing the speed to continue the second stirring; (3) reducing the rotation speed, adding a sterilizing agent and a defoaming agent during the third stirring, filtering, and obtaining the aqueous latex.
4. The preparation method according to claim 3, characterized in that: In step (2), the first stirring speed is 600-800 r / min, and the stirring time is 5-10 min; And / or, the second stirring speed is 1300-1800 r / min, and the stirring time is 20-50 min.
5. The preparation method according to claim 3, characterized in that: In step (3), the rotation speed of the third stirring is 800-1300 r / min, and the stirring time is 5-15 min.
6. A construction method of the water-based latex according to claim 1 or 2, characterized in that: The method comprises coating the water-based latex on the air leakage location.
7. The construction method according to claim 6, characterized in that: The method comprises applying glue on the mold joint seam of the upper and lower box bodies of the composite material packaging box, or applying glue on the flange between the box body and the box cover, or applying glue on the entire box.
8. The construction method according to claim 7, characterized in that: The glue coating method includes first coating along the X-axis direction, drying the first time, coating the second time along the Y-axis direction, drying the second time, coating the third time along the X-axis direction, drying the third time to form a glue film.
9. The construction method according to claim 8, characterized in that: The first drying time is 20 to 40 minutes, the second drying time is 20 to 40 minutes, and the third drying time is 1 to 3 hours.
10. The construction method according to claim 8, characterized in that: The thickness of the adhesive film is 0.2-1 mm.
Citation Information
Patent Citations
Multiple-effect latex anti-gas migration agent for deep well cementing in oil field and preparation method thereof
CN103834374A
Anion styrene-butadiene latex channeling-preventing agent for oil well cementing and preparation method thereof
CN105086970A
Styrene-butadiene latex adhesive and preparation method thereof
CN105440975A
Coating technology of coating of flange sealing surface
CN105782639A
Modified styrene-butadiene latex and preparation method thereof
CN112552452A